A 5‐year cohort study on early implant placement with guided bone regeneration or alveolar ridge preservation with connective tissue graft. (17th September 2020) - Wessels, Retief; Vervaeke, Stijn; Seyssens, Lorenz; Eghbali, Aryan; Cosyn, Jan
Abstract: Purpose: To assess on the one hand the 5‐year outcome of early implant placement with guided bone regeneration (EIP/GBR) and on the other hand of alveolar ridge preservation with late implant placement and connective tissue graft (ARP/CTG). Materials and methods: Patients who had been treated with a single implant in the anterior maxilla in 2014 were selected for reevaluation in 2019. In the EIP/GBR cohort, implants were installed 4 to 8 weeks following extraction and the buccal contour was overbuilt by means of GBR. In the ARP/CTG cohort, collagen‐enriched deproteinized bovine bone mineral was applied at the time of extraction and implants were installed 5 months later. All ARP/CTG cases received a buccal CTG 3 months after implant installation to reestablish buccal convexity. Primary outcomes were the pink esthetic score (PES) (Belser et al 2009) and the mucosal scarring index (MSI) (Wessels et al 2019). Clinical and radiographical parameters were secondary outcomes. Results: Eighteen patients (9 females; mean age 52) in the EIP/GBR cohort, and 20 patients (9 females; mean age 38) in the ARP/CTG cohort were evaluated. PES was 6.28 following EIP/GBR. A (nearly) perfect aesthetic outcome defined as PES ≥8 was found in 3/18 cases. Perfect root convexity / soft tissue color and texture seemed most difficult to achieve. PES was 7.80 following ARP/CTG. A (nearly) perfect aesthetic outcome was found in 11/20 cases. MSI was 2.94 following EIP/GBR with 14/18 cases showing scarring. MSI yielded 0.50 following ARP/CTG with 6/20 cases showing scarring. In both cohorts, all implants survived, and none had developed periimplantitis. However, implants in the ARP/CTG cohort demonstrated a 5.4 times higher risk for periimplant mucositis than implants in the EIP/GBR cohort at 5 years follow‐up. Conclusion: EIP/GBR and ARP/CTG showed acceptable long‐term outcomes. The aesthetic outcome was particularly favorable following ARP/CTG, yet this should be interpreted with caution due to selection bias and because soft tissue grafting was not performed in the EIP/GBR cohort. Randomized controlled trial (RCTs) comparing EIP with ARP are required to assess the need for soft tissue grafting and to evaluate clinical, aesthetic, volumetric, and patient‐reported outcomes. Only on the basis of such studies clinical recommendations can be made.